Understanding the Intellectual Structure and Evolution of Distributed Leadership in Schools: A Science Mapping-Based Bibliometric Analysis - Karakose, Turgut; Papadakis, Stamatios; Tulubas, Tijen; Polat, Hakan (Mdpi, 2022)
Distributed leadership (DL) has currently generated significant interest among researchers considering that schools have become too complex to be led by a single leader, and school leadership activity is already distributed in nature. Numerous studies have contributed to this knowledge base through empirical and conceptual investigations. Our study aims to demonstrate the bibliometric performance, intellectual architecture, and strategic themes of this field, with a particular focus on DL in schools. Our dataset includes 221 articles published between 2002 and 2021 on the Web of Science (WoS) database. Science mapping analysis was conducted using SciMAT to map the conceptual structure and thematic evolution of the research field, and applied for three consecutive periods so as to be able to compare/contrast the changing thematic trends. Bibliometric performance analysis was also employed in order to determine the distribution of related publications by years, the number of accumulated publications, the average number of citations per article, and the most productive/cited authors and journals. The results indicated that research on DL in schools has grown substantially over the past decade, and that the thematic structure has fundamentally evolved from school improvement/effectiveness and commitment to teachers and instructional leadership, innovation, and capacity-building in schools.
Keywords: distributed leadership; leadership; school management; bibliometric analysis; science mapping; SciMAT